Direct electrochemistry of doxorubicin and its ultra-sensitive detection using a novel porous thorny carbon dodecahedron. (21st November 2022) - Ouyang, Yongchang; Liang, Miao; Wang, Fangzhen; Mei, Songqing; Mo, Guangquan
Abstract : Novel polyhedron was prepared for the high-performance electrocatalysis and detection of doxorubicin, leading to the successful doxorubicin sensing in HeLa cell inhibition. Abstract : Herein, supported by the attractive structure of zeolitic imidazolate frameworks (ZIFs), novel porous thorny carbon dodecahedron implanted with hollow cobalt oxide nanospheres (PCD-HC) was prepared by the two-step pyrolysis of ZIFs. Morphology and structure investigations showed that PCD-HC was a highly porous rhombic dodecahedron embedded with hollow nanospheres. Elemental mapping revealed that the main dodecahedral structure of PCD-HC was a carbonized framework doped with N species. Besides, well-defined hollow Co3 O4 nanospheres with abundant O vacancies were implanted. Due to the highly porous structure, embedded active species, and graphite-like structure, PCD-HC displayed distinguished electrocatalysis towards doxorubicin (DOX) with a pair of highly symmetric redox peaks and fast direct electron transfer of anthracycline. The direct electrochemistry and catalytic mechanism of the DOX redox reaction at PCD-HC were elucidated, and a PCD-HC based electrochemical sensor was developed for the DOX sensing with a broad linear range from 1.0 nM to 1.0 μM. The limit of detection was obtained as 0.15 nM (S/N = 3). Besides, PCD-HC sensor also displayed a wide detection range at a high concentration from 2.0 to 12.0 μM. Moreover, PCD-HC sensor presented a high selectivity with strong anti-interference capability towards common inorganic ions and small biomolecules. The reproducibility, repeatability, and stability were examined with satisfactory results. Significantly, a PCD-HC sensor was applied in the monitoring of DOX in HeLa cells inhibiting process, indicating a substantial detection platform for DOX sensing.